The Hasimoto Surface According to Bishop Frame - Kelleci, Alev; Bektaş, Mehmet; Ergüt, Mahmut (Adiyaman University, 2019)
In this paper, we investigate the Hasimoto surfaces in Euclidean 3-space. Firstly, we investigate the geometric properties of these surfaces in Euclidean 3-space. Especially, we obtain the curvatures of Hasimoto surface according to Bishop frame. Then we give some characterization of parameter curves obtained according to Bishop frame of Hasimoto surfaces. © 2019, Adiyaman University. All rights reserved.
Bishop Çatısı ile İlişkilendirilmiş Hasimoto Yüzeyleri
Keywords: Bishop frame; Hasimoto surfaces; Smoke ring equation